2008
DOI: 10.5650/jos.57.321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Heated with Gluten on Weight-Loss Dieting. I.

Abstract: Fresh oil was heated for 20 h at 180 with amino acids or gluten. A powdered diet (AIN93G; no fat) was mixed with 7 wt% of fresh oil (control), or supernatants of the heated oils described above, and fed to male Wistar rats for 12 weeks. No gross symptoms attributable to the heated oils were observed, but the gluten group showed a slow body weight increase; a significant difference was found in the weight after age 21 weeks in spite of diet consumption comparable to that of the control group. The serum of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Our approach 3,33) to creating a safe and effective oil for weight-loss dieting was that a part of the oil was not fully hydrolyzed by lipase, resulting in decreased absorption and increased amounts of excreted oil. The result from the present study proved our approach described above.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach 3,33) to creating a safe and effective oil for weight-loss dieting was that a part of the oil was not fully hydrolyzed by lipase, resulting in decreased absorption and increased amounts of excreted oil. The result from the present study proved our approach described above.…”
Section: Discussionmentioning
confidence: 99%
“…Using a blender, the latter was mixed uniformly with 7 wt% of experimental oils and fresh oil, respectively. The three kinds of diets, thus prepared, were handled and provided as described in our paper [1][2][3][4][5][6] . All the diets were used after radio-sterilization.…”
Section: Dietsmentioning
confidence: 99%
“…We heated oil with amino acids, gluten, sucrose, or wheat starch at 180 for 20 h 1,2) . Among the oils obtained, only the oil heated with gluten had a mild odor; the others had a rancid odor.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the substances should be soluble in oil and effective in very limited quantities. Soybean protein employed in the present study contained various components other than protein, but it has been confirmed 20,21) that the body weightloss promoting effects in excess of those from protein were not expected from amino acids, sucrose, and carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the substances should be soluble in oil and effective in very limited quantities. Soybean protein employed in the present study contained various components other than protein, but it has been confirmed 20,21) that the body weightloss promoting effects in excess of those from protein were not expected from amino acids, sucrose, and carbohydrates.Dieting oils presently marketed around the world contain Salatrim ®22) , Caprenin ®23) , Olestra ®24,25) , Econa ®26-28) and Healthy Resetta ®29-31) . Salatrim ® , Caprenin ® , and Healthy Resetta ® are triacylglycerides esterified with long and short (medium) chain fatty acids.…”
mentioning
confidence: 99%